Islamic Discourse in The Mode of Populism - Fahmy Farid Purnama (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2019)
This article attempts to elaborates the trajectory of ummah consciousnesses that attached to contemporary Islamic discourse in the mode of populism. In contemporary world which technology forms and accelerates human life, populism has become a tool of progressives, of reactionaries, of democrats, of autocrats, of the right and even of the left. Its adaptability lies in the ‘empty heart’ of populism: populism lacks a commitment to key values. By conceptualizing the phenomenon as dynamic and ideologically variable within the discourse horizon, this article seeks to a better understanding of the trajectory of Islamic discourse in the mode of populism, its causes and implications of the populist turn in contemporary world.